PELATIHAN PERENCANAAN SDM BERBASIS EKONOMI SYARIAH UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA BOJONGSARI - Paroli Paroli; Suca Rusdian (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This Community Service Program (PkM) was conducted in Bojongsari Village, Bojongsoang District, Bandung Regency, aiming to strengthen human resource (HR) planning capacity and Islamic economics literacy as an effort to improve community quality of life. The identified problems included unclear skill mapping and development targets, unstructured role distribution in productive activities, poor financial management practices due to limited bookkeeping, and an Islamic economics understanding that remained general rather than practical. A participatory approach was applied through initial observation and needs assessment, focus group discussions, interactive training, case studies, hands-on practice using worksheets, and evaluation using pretest–posttest and participant satisfaction questionnaires. The program results indicate improved participant understanding (reflected by higher posttest scores than pretest scores), completion of HR planning and simple financial recording worksheets, and the formulation of follow-up action plans as implementation commitments. These findings are important because the program offers an integrated and practical intervention model to enhance village community capacity and economic decision-making in a more orderly, fair, and sustainable manner.